Facilitating Mitochondrial Calcium Uptake Improves Activation-Induced Cerebral Blood Flow and Behavior after mTBI - Murugan, Madhuvika; Santhakumar, Vijayalakshmi; Kannurpatti, Sridhar S. (Frontiers in Systems Neuroscience, 2016)
Mild to moderate traumatic brain injury (mTBI) leads to secondary neuronal loss via excitotoxic mechanisms, including mitochondrial Ca2+ overload. However in the surviving cellular population, mitochondrial Ca2+ influx and oxidative metabolism are diminished leading to suboptimal neuronal circuit activity and poor prognosis. Hence we tested the impact of boosting neuronal electrical activity and oxidative metabolism by facilitating mitochondrial Ca2+ uptake in a rat model of mTBI. In developing rats (P25-P26) sustaining an mTBI, we demonstrate post-traumatic changes in cerebral blood flow (CBF) in the sensorimotor cortex in response to whisker stimulation compared to sham using functional Laser Doppler Imaging (fLDI) at adulthood (P67-P73). Compared to sham, whisker stimulation-evoked positive CBF responses decreased while negative CBF responses increased in the mTBI animals. The spatiotemporal CBF changes representing underlying neuronal activity suggested profound changes to neurovascular activity after mTBI. Behavioral assessment of the same cohort of animals prior to fLDI showed that mTBI resulted in persistent contralateral sensorimotor behavioral deficit along with ipsilateral neuronal loss compared to sham. Treating mTBI rats with Kaempferol, a dietary flavonol compound that enhanced mitochondrial Ca2+ uptake, eliminated the inter-hemispheric asymmetry in the whisker stimulation-induced positive CBF responses and the ipsilateral negative CBF responses otherwise observed in the untreated and vehicle-treated mTBI animals in adulthood. Kaempferol also improved somatosensory behavioral measures compared to untreated and vehicle treated mTBI animals without augmenting post-injury neuronal loss. The results indicate that reduced mitochondrial Ca2+ uptake in the surviving populations affect post-traumatic neural activation leading to persistent behavioral deficits. Improvement in sensorimotor behavior and spatiotemporal neurovascular activity following kaempferol treatment suggests that facilitation of mitochondrial Ca2+ uptake in the early window after injury may sustain optimal neural activity and metabolism and contribute to improved function of the surviving cellular populations after mTBI